Cartoons from Thairath newspaper (Between August 2554 to Febuary 2557) - Sarakun, Numfhon; Sritunma, Kritsada; Kedthed, Boonyong (Academic MCU Buriram Journal, 2017)
This research with the objectives of the link to conten analysis and communication stnategies of comics from Thairath newspaper. Data in analysis is a cartoon from the Thairath newspaper by (Somchai Katunyutanun) and Sai (Sakda Saeeiaw) between August 2554 to Febuary 2557 amount 853 copies. The concept in this research. This concept is about the classificstion Caricature, by Kanokporn Chantharamongkol, Theera Thanyaphiboon and the concept of communicdtion in order to convey humor by Phrasobchoke Nawaphanphipat by referring to (Polly Keener) This result showed that the content of the cartoon from Thairath newspaper have subject matter from nigh to low as follows The content of political, social, economic, aspect of international relations and cultural and education content. The section strategies of communication assembly langvage of the cartoon from Thairath newspaper by that include decending comment that is unexpected and ridicvle the inverse the words that conflict with the feeling that should be In compatibility Mimicry and imitation The pun and comparison Exageration or less true fear or a pathetic moments to chage the human are animals or things. Incorrect according to propriety. And the manner in which the cartoon characters don’t notice but readers Know respectively. The result of this research In addition to know the content of the cartoon and strategies for communication assemble of the cartoon and this research will be useful to those interested in assemble analysis of the cartoon in daily newspaper and the following can be utilized in learning or teaching in Thai language subject that used in a daily newspaper.